E-SKHBK untuk Optimalisasi Pemutusan Hubungan Kerja di PT Sumber Alfaria Trijaya Tbk: Optimizing Termination of Employment: Implementation of Personal Extreme Programming and Evaluation of EUCS PIECES - Adhira Putri, Dhivanny; Trezandy Lapatta, Nouval (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
For 24 years of operation, Alfamart has always upheld the company’s values to provide customer satisfaction. However, efforts to manage human resources as the main asset are needed to support the company’s values in achieving its goals. One of the crucial aspects in this effort is the Personnel Division, which is responsible for employee administration. Unfortunately, the process of terminating employment is still done manually and conventionally. This research explores the development of the Employment Termination Letter (e-SKBHK) website as a solution to optimize the termination process by enhancing efficiency, minimizing paper usage, and ensuring letter security through QR codes. The website development is carried out using the Personal Extreme Programming method, adapted from Extreme Programming but tailored for a single developer. This website development uses PHP language with Laravel 10 framework that applies Model View Controller architecture pattern. The test results using the EUCS method show that users are satisfied with the website developed with an average score of 4.3. While testing with the PIECES method shows a significant increase from a score of 1.96 on the current mail management system to 4.07 on the developed website. This confirms the successful implementation of the website in the aspects of performance, information, economy, control, efficiency, and service in mail management.